If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 6) = 102 Reorder the terms: (6 + 4x) = 102 Remove parenthesis around (6 + 4x) 6 + 4x = 102 Solving 6 + 4x = 102 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 4x = 102 + -6 Combine like terms: 6 + -6 = 0 0 + 4x = 102 + -6 4x = 102 + -6 Combine like terms: 102 + -6 = 96 4x = 96 Divide each side by '4'. x = 24 Simplifying x = 24
| 6u-9=15 | | 6=y-5x | | 3(9h+5)= | | 2b+15=3b+7 | | 24i-18=5 | | 7x-3+y=27 | | x^2/0=1 | | (3z-5)(8-z)=0 | | y=6(3)-13 | | 4p/10=20 | | 5z(4z+3)=150 | | 4x+23=21x-1 | | x-4)(x-4)/x^2-3x-15=47 | | (x-4)(x-4)/x^2-3x-15 | | whatisx+5=10 | | 150=41+x | | 8x-4=2x | | f(x)=0.25x^4-2x^3 | | 11/x-5=3 | | 25=30y | | 4.3/1.9 | | 10/x=13 | | 2=-6x+15y | | -0.45/1.8=0.81/z | | 2e^15x=11 | | 7x-(4x+32)=12 | | (5/6)x-3=7 | | 1/x=-13 | | (18n)(5)= | | -6-1/2p=8 | | -5(4x+3)= | | 62=-7a-43 |